Nevarnosti in ugotavljanje hipervitaminoz askorbinske kisline in vitamina D - Muminović, Boštjan (Farmacevtski vestnik, 2017)
Vitamins C and D are very common as dietary supplements in healthy people who have good nutrition habits, even though actual beneficial properties of these products have not been demonstrated. Usage of these dietary supplements is, in most cases, chronic and not controlled by medical professionals, which can result in toxic effects due to metabolism and accumulation of vitamins and their products in the human body. This article will interpret dangers of hypervitaminosis of ascorbic acid and vitamin D, how to determine them and the effects of hypervitaminosis on the human body.
Keywords: hipervitaminoza; toksični učinki; vitamin; vitamin C; Vitamin D; Vitamini